ORGANOLEPTIC QUALITY CHARACTERISTICS OF RISSOLE FROM BY-PRODUCTCATFISH FILLET PROCESSING (Pangasius hypophthalmus) - Melania Syahada; Dewita Dewita; Desmelati Desmelati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
ABSTRACTThis study aimed to analyze the effect of adding catfish fillet by-products on the organoleptic quality characteristics of rissole. The research method was the experiment using a non-factorial Complete Randomized Design (CRD) with 4 levels of treatment, namely R0 (without a by-product of catfish fillet), R1 (250 grams by-product of catfish fillet), R2 (500 grams by-product of catfish fillet), R3 (750 grams by-product of catfish fillet). The tested parameters performed were organoleptic analysis (appearance, odor, taste, and texture) and proximate analysis (moisture content, ash content, protein content, and fat content). The results showed that the addition of catfish fillet by-products had a significant effect significant (p<0.05) on the quality characteristics of rissole. (R1) 250 grams was the best treatment with the characteristics of intact, attractive rissoles, and a brownish yellow color appearance, has a distinctive scent of rissoles with a hint of fish; a specific taste typical of the rissole and catfish, and distinctive taste of fish, tasty, good flavor; and the texture is compact and crispy. Furthermore, proximate value of R1 was 53,80% moisture content, 1,37% ash content, 6,93% protein content, and 3,71% fat content.Keywords: by-product, characteristics, rissoles, scrape meat.